Esensi Interaksi Visual dalam Dunia Facebook yang Virtual - Noval Sufriyanto Talani (Jurnal Komunikasi, 2014)
This article discusses the phenomenon of interaction on Facebook. This study used a subjective approach with a qualitative research method through the analysis of the phenomenology and symbolic interaction. The study was conducted to determine the essential meaning of symbolic interaction that occurs in the world of Facebook. Through in-depth interviews of 10 people found that Facebook users are interchangeable symbols emoticons users to interact on Facebook has a contextual meaning. At different users’ of a symbol can have different meanings so the meaning is no longer unconventional, but personal. This is caused by the user freedom in using or producing personal emoticon symbols as an expression of nonverbal cues. Essentially, the interaction on Facebook is the visual interaction. Through visual, users’ can display a variety of actions on Facebook including symbolic impression management. Impression management on Facebook is heavily influenced intentional relationship between physical self as a subject in the real world and themselves become symbolic objects in the virtual world. This relationship is illustrated by a model of interaction and symbolic impression management model in the virtual world of Facebook.